Do Consumers Pay More Using Debit Cards than Cash? An Experiment - Emma Runnemark; Jonas Hedman; Xiao Xiao (Lund University, School of Economics and Management, Department of Economics, 2014)
We conduct an incentivized experiment to test whether the willingness to pay is higher for debit cards compared to cash for three consumer products. Our findings support this conjecture also after controlling for cash availability, spending type, price familiarity and consumption habits of the products. The evidence thus suggests that different representations of money matters for consumer behavior.
Keywords: D03; D10; E42; 330; payment methods; debit cards; cash; willingness-to-pay